2022
DOI: 10.3390/catal12101163
|View full text |Cite
|
Sign up to set email alerts
|

Recent Strategies in Nickel-Catalyzed C–H Bond Functionalization for Nitrogen-Containing Heterocycles

Abstract: N-heterocycles are ubiquitous in natural products, pharmaceuticals, organic materials, and numerous functional molecules. Among the current synthetic approaches, transition metal-catalyzed C–H functionalization has gained considerable attention in recent years due to its advantages of simplicity, high atomic economy, and the ready availability of starting materials. In the field of N-heterocycle synthesis via C–H functionalization, nickel has been recognized as one of the most important catalysts. In this revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…A related review covering Ni-catalyzed C-H bond functionalization reactions was reported [54]. The recent review specifically addressed intramolecular and intermolecular Ni-catalyzed functionalization reactions towards synthesis of N-containing heterocycles in the period 2008-2021 [54].…”
Section: Introductionmentioning
confidence: 99%
“…A related review covering Ni-catalyzed C-H bond functionalization reactions was reported [54]. The recent review specifically addressed intramolecular and intermolecular Ni-catalyzed functionalization reactions towards synthesis of N-containing heterocycles in the period 2008-2021 [54].…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen containing cyclic compounds widely exist in various natural products and pharmaceutical molecules. The catalytic C-H functionalization of heterocycles [52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70] is a straightforward and economic route to achieve post-modification of drugs and active molecules. And the introduction of dimethylallyl-related units (C5 skeletons) [71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88] into functional molecules often leads to dramatic changes in their lipophilicities and metabolic stabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Prompted by the seminal stoichiometric work of Kleiman and Dubeck, the recent years have witnessed significant progress in Ni-catalyzed C­(sp 2 )–H functionalization reactions. , Unlike other metals in the d 10 series, the reactivity of nickel catalysts in C­(sp 2 )–H functionalization remain predominantly confined to the utilization of proximal, yet strongly coordinating, directing groups, with bond formation occurring at the ortho position (Scheme , top) . Despite the advances realized, particularly in Catellani-type reactions, the means to enable distal C­(sp 2 )–H functionalization aided by Ni species without recourse to directing groups, acidic C­(sp 2 )–H bonds, or aryl halides still remains unexplored, particularly with phenol C–O derivatives as traceless entities (path b) …”
mentioning
confidence: 99%